Isaiah 1-12 - Bartelt, Andrew H. (Concordia commentary a theological exposition of sacred scripture, 2024)
"This scholarly commentary on Isaiah 1-12 begins with an introduction that discusses the literary structure and message. For each passage it provides an original translation, textual notes that analyze lexical and grammatical issues in the Hebrew text and ancient versions, followed by historical and theological commentary. Each section explains how the passage relates to the rest of Isaiah 1-66 and concludes with theological reflections on the interconnections within Scripture as a whole. The author interacts with the full range of biblical scholarship. The prophet Isaiah was inspired by the Holy Spirit to speak the Word of God, relevant for the people of God throughout the centuries for contemporary reflection and application. Isaiah 1-12 focuses on Immanuel, "God with us," the Word now become flesh in Jesus Christ"--